PENGARUH MANAJEMEN STRES DAN STATUS PEKERJAAN IBU TERHADAP PENGASUHAN ANAK USIA SEKOLAH SAAT PANDEMI COVID-19 - Naziah, Hilma Rosmy; Sunarti, Euis; Riany, Yulina Eva (Jurnal Ilmu Keluarga dan Konsumen, 2023)
The COVID-19 pandemic has become a challenge for parents which can increase stress levels and have a negative impact on parenting. This study aims to analyze differences in parenting and stress management consisting of individual sources of stress, sources of parenting stress, coping strategies, and stress based on the type of mother's occupation and analyze the effect of family characteristics, child characteristics, and stress management on parenting. The research design used a cross-sectional study and involved a sample of 47 working mothers and 53 housewives who came from intact families and had children who were still studying at the state elementary school level. Based on the results of the study, there were no significant differences in all variables based on the type of mother's occupation. Family characteristics have a significant positive effect on parenting. The higher the education of parents and family income, the higher the quality of parenting. Sources of parenting stress and symptoms of stress have a significant direct effect on parenting. Sources of individual stress have a significant indirect effect on parenting. Therefore, the higher the sources of stress and symptoms of stress, the lower the quality of parenting during the COVID-19 pandemic.